1,2-GG intrastrand cross-link of antitumor dinuclear bifunctional platinum compound with spermidine linker inhibits DNA polymerization more effectively than the cross-link of conventional cisplatin - Moriarity, Branden; Nováková, Olga; Farrell, Nicholas; Brabec, Viktor; Kaspárková, Jana (Archives of biochemistry and biophysics, 2007)
In order to learn more about the molecular basis for the inhibition of DNA replication produced by antitumor platinum drugs, we investigated DNA polymerization using DNA templates site-specifically modified with the 1,2-GG intrastrand cross-link of dinuclear bifunctional [{trans-PtCl(NH(3))(2)}(2){l-spermidine-N1,N8}](3+)(BBR3571) or conventional mononuclear cisplatin. These cross-links which have the same nature, but differ in the size and character of the conformational alteration induced in double-helical DNA, were analyzed for bypass ability with reverse transcriptase of human immunodeficiency virus type 1 and Klenow fragment of DNA polymerase I deficient in exonuclease activity. We found that the 1,2-GG intrastrand CL of BBR3571 inhibited DNA translesion synthesis markedly more than the same adduct of cisplatin. This result was explained by a larger size of the cross-link of BBR3571 and by a flexibility induced in DNA by this cross-link which can make the productive binding of this adduct at the polymerase site more difficult.
Keywords: protinádorové látky; konformace nukleové kyseliny; cisplatina; organoplatinové sloučeniny; DNA Damage; Cisplatin; DNA; oligonukleotidy; Cross-Linking Reagents; Organoplatinum Compounds; Oligonucleotides; Nucleic Acid Conformation; Antineoplastic Agents; poškození DNA; reagencia zkříženě vázaná